Chronic Hepatitis C Virus Infection: A Review of Current Direct-Acting Antiviral Treatment Strategies - Zhang, MD, Jonathan; Nguyen, MD, Douglas; Hu, MD, Ke-Qin (North American Journal of Medicine and Science, 2016)
Chronic Hepatitis C virus (HCV) infection carries a significant clinical burden in the United States, affecting more than 4.6 million Americans. Untreated chronic HCV infection can result in cirrhosis, portal hypertension, and hepatocellular carcinoma. Previous interferon based treatment carried low rates of success and significant adverse effects. The advent of new generation oral antiviral therapy has led to major improvements in efficacy and tolerability but has also resulted in an explosion of data with increased treatment choice complexity. Treatment guidelines are constantly evolving due to emerging regimens and real world treatment data. There also still remain subpopulations for whom current treatments are lacking or unclearly defined. Thus, the race for development of HCV treatment regimens still continues. This review of the current literature will discuss the current recommended treatment strategies and briefly overview next generation agents. [N A J Med Sci. 2016;9(2):47-54. DOI: 10.7156/najms.2016.0902047]